Nitrogen limitation-induced adaptive response and lipogenesis in the Antarctic yeast Rhodotorula mucilaginosa M94C9 - Rosas-Paz, Miguel; Zamora-Bello, Alberto; Torres-Ramírez, Nayeli; Villarreal-Huerta, Diana; Romero-Aguilar, Lucero; Pardo, Juan Pablo; El Hafidi, Mohammed; Sandoval, Georgina; Segal-Kischinevzky, Claudia; González, James (Frontiers in Microbiology, 2024)
The extremotolerant red yeast Rhodotorula mucilaginosa displays resilience to diverse environmental stressors, including cold, osmolarity, salinity, and oligotrophic conditions.Particularly, this yeast exhibits a remarkable ability to accumulate lipids and carotenoids in response to stress conditions. However, research into lipid biosynthesis has been hampered by limited genetic tools and a scarcity of studies on adaptive responses to nutrient stressors stimulating lipogenesis. This study investigated the impact of nitrogen stress on the adaptive response in Antarctic yeast R. mucilaginosa M94C9. Varied nitrogen availability reveals a nitrogen-dependent modulation of biomass and lipid droplet production, accompanied by significant ultrastructural changes to withstand nitrogen starvation. In silico analysis identifies open reading frames of genes encoding key lipogenesis enzymes, including acetyl-CoA carboxylase (Acc1), fatty acid synthases 1 and 2 (Fas1/Fas2), and acyl-CoA diacylglycerol O-acyltransferase 1 (Dga1). Further investigation into the expression profiles of RmACC1, RmFAS1, RmFAS2, and RmDGA1 genes under nitrogen stress revealed that the prolonged upregulation of the RmDGA1 gene is a molecular indicator of lipogenesis. Subsequent fatty acid profiling unveiled an accumulation of oleic and palmitic acids under nitrogen limitation during the stationary phase. This investigation enhances our understanding of nitrogen stress adaptation and lipid biosynthesis, offering valuable insights into R. mucilaginosa M94C9 for potential industrial applications in the future.